Analiza posledic ukrepa zaprtja šol in vrtcev v času epidemije covid-19 z vidika plačne vrzeli in možnosti za dostop do trga dela - Pensa, Iris (Podjetje in delo, 2021)
The authors focus on the question of what consequences the measure of closing schools and kindergartens has for parents, especially mothers, in terms of the pay gap and equal opportunities in accessing the labour market. In doing so, they question whether the measures taken during the coronavirus epidemic are in fact the same for everyone or whether they have a greater effect on a particular group of people. The authors find that the measure of closing schools and kindergartens affected parents with younger children significantly more than those who did not have children. Researches also show that the measure affected women more than men. Thus, the authors conclude that the measure of closing schools and kindergartens is indirectly discriminatory. The authors then explain what conditions must be met for a measure to be constitutional and permissible despite discrimination. The authors question whether an adequate proportionality test was carried out before the adoption of the school and kindergarten closure measure, taking into account the aspect of discrimination, and point out that the aspect of gender and unequal employment opportunities of parents, especially women, must be taken into account in order to pursue the goal of equal treatment and the reduction of the pay gap.
Keywords: COVID-19 epidemic; discrimination; diskriminacija; epidemija covid-19; indirect discrimination; načelo enakega plačila žensk in moških; pay discrimination; pay gap; plačna diskriminacija; plačna vrzel; posredna diskriminacija; principle of equal pay for women and men